Polarizer with phase difference layer and image display device with polarizer with phase difference layer
Patent Information
- Application Number
- JP2023126536
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
【0006】 本発明の実施形態によれば、干渉ムラおよび打痕の発生が抑制された位相差層付偏光板を提供し得る。
Smart Images

Figure 2025022189000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing plate with a retardation layer and an image display device having the polarizing plate with a retardation layer. [Background technology]
[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices), are rapidly becoming popular. In these image display devices, a polarizing plate with a retardation layer is used for the purpose of improving display characteristics and preventing reflection. The polarizing plate with a retardation layer can usually be laminated on an image display panel via an adhesive layer. A substrate, wiring, etc. are arranged on the surface of the image display panel. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-14611 Summary of the Invention [Problem to be solved by the invention]
[0004] When a polarizing plate with a retardation layer is bonded to an image display panel, dents may occur on the viewing side (i.e., the side not in contact with the image display panel) of the polarizing plate with a retardation layer. The retardation layer, which is an alignment and solidification layer of a liquid crystal compound, is thinner than a retardation layer made of a resin film, so that dents tend to occur easily. In addition, when two or more retardation layers, which are liquid crystal alignment and solidification layers, are laminated, interference unevenness may become a problem. In order to suppress interference unevenness, it is known to dispose a pressure-sensitive adhesive layer between the retardation layers. However, when a pressure-sensitive adhesive layer is disposed, dents may become more noticeable. The main object of the present invention is to provide a polarizing plate with a retardation layer that achieves both suppression of interference unevenness and suppression of dents. [Means for solving the problem]
[0005] 1. A polarizing plate with a retardation layer according to an embodiment of the present invention includes, in this order, a polarizing plate including a polarizer; a first retardation layer which is a layer with a solidified alignment of a liquid crystal compound; an adhesive layer; and a second retardation layer which is a layer with a solidified alignment of a liquid crystal. A slow axis of the first retardation layer intersects with a slow axis of the second retardation layer and also intersects with an absorption axis of the polarizer. The adhesive layer has a thickness of 2 μm to 8 μm. 2. In the retardation layer-attached polarizing plate according to the above item 1, the adhesive layer may be a pressure-sensitive adhesive layer. 3. In the polarizing plate with a retardation layer described in 1 or 2 above, the polarizing plate may include a first protective layer laminated on one surface of the polarizer, and a second protective layer laminated on the other surface of the polarizer. 4. In the retardation layer-attached polarizing plate according to any one of the above 1 to 3, the polarizing plate may have a thickness of 45 μm to 85 μm. 5. In the retardation layer-attached polarizing plate according to any one of the above 1 to 4, the polarizing plate may be laminated to the first retardation layer via an adhesive layer. 6. In the polarizing plate with a retardation layer according to any one of 1 to 5 above, the first retardation layer may have Re(550) of 200 nm to 300 nm, the angle between the slow axis of the first retardation layer and the absorption axis of the polarizer may be 10° to 20°, the second retardation layer may have Re(550) of 100 nm to 190 nm, and the angle between the slow axis of the second retardation layer and the absorption axis of the polarizer may be 70° to 80°. 7. In another aspect of the present invention, there is provided an image display device. The image display device of the embodiment of the present invention includes the retardation layer-attached polarizing plate according to any one of 1 to 6 above. 8. The image display device according to the above item 7 may be an organic electroluminescence display device. Effect of the Invention
[0006] According to the embodiment of the present invention, it is possible to provide a retardation layer-attached polarizing plate in which the occurrence of interference unevenness and dents is suppressed. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.
[0010] A. Overall structure of the polarizing plate with a retardation layer The retardation layer-attached polarizing plate of the present invention includes, in this order, a polarizing plate including a polarizer; a first retardation layer which is an alignment-solidified layer of a liquid crystal compound; an adhesive layer; and a second retardation layer which is a liquid crystal alignment-solidified layer. FIG. 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. The retardation layer-attached polarizing plate 100 of the illustrated example includes, in this order, a polarizing plate 10 including a polarizer 11; an adhesive layer 21; a first retardation layer 31 which is an alignment-solidified layer of a liquid crystal compound (hereinafter, also referred to as a liquid crystal alignment-solidified layer); an adhesive layer 40; and a second retardation layer 32 which is a liquid crystal alignment-solidified layer. The polarizing plate 10 typically includes a polarizer 11, a first protective layer 12 laminated on one surface of the polarizer 11, and a second protective layer 13 laminated on the other surface of the polarizer 11. The second protective layer 13 may be omitted. For example, when the first retardation layer 31 can also function as a protective layer, the protective layer 13 may be omitted. In the illustrated example, the polarizing plate 10 is laminated with the first retardation layer 31 via the adhesive layer 21. In the retardation layer-attached polarizing plate 100, the slow axis of the first retardation layer 31 and the slow axis of the second retardation layer 32 cross each other, and the slow axis of the first retardation layer 31 and the absorption axis of the polarizer 11 cross each other. For example, as described later, the angle between the slow axis of the first retardation layer 31 and the absorption axis of the polarizer 11 may be 10° to 20°, and the angle between the slow axis of the second retardation layer 32 and the absorption axis of the polarizer 11 may be 70° to 80°. The thickness of the adhesive layer 40 is 2 μm to 8 μm. In this specification, the adhesive layer refers to an adhesive layer or a pressure-sensitive adhesive layer. In the illustrated example, the adhesive layer 40 is a pressure-sensitive adhesive layer. The retardation layer, which is a liquid crystal alignment solidified layer, is thin and can contribute to the thinning of the retardation layer-attached polarizing plate. On the other hand, a problem of dents occurring when the plate is attached to a liquid crystal panel may occur. In addition, in a retardation layer-attached polarizing plate including a plurality of retardation layers, which are liquid crystal alignment solidified layers, the retardation layers may cause thin film interference, resulting in interference unevenness. As a method for eliminating interference unevenness, for example, a pressure-sensitive adhesive layer is known to be disposed between the retardation layers, which are liquid crystal alignment solidified layers. However, when a pressure-sensitive adhesive layer is disposed, the occurrence of dents during attachment to a liquid crystal panel may become more prominent. Therefore, it may be difficult to simultaneously suppress the occurrence of dents and the suppression of interference unevenness.As described above, in the polarizing plate with a retardation layer according to the embodiment of the present invention, an adhesive layer having a thickness of 2 μm to 8 μm is disposed between the retardation layers, which are liquid crystal alignment solidified layers. With such a polarizing plate with a retardation layer, it is possible to provide a polarizing plate with a retardation layer that can simultaneously suppress the occurrence of dents and suppress interference unevenness, which have been difficult to achieve up until now.
[0011] The retardation layer-attached polarizing plate may further include another retardation layer in addition to the first retardation layer and the second retardation layer. The other retardation layer may be typically provided on the outside of the second retardation layer 32 (the side opposite to the polarizer 10). The optical properties (e.g., refractive index properties, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement position, and the like of the other retardation layer may be appropriately set according to the purpose. The refractive index properties of the other retardation layer typically have the relationship nz>nx=ny.
[0012] The retardation layer-attached polarizing plate 100 may have an adhesive layer 50 as the outermost layer. The retardation layer-attached polarizing plate 100 can be attached to an image display device (substantially, an image display panel) via the adhesive layer 50. For practical purposes, it is preferable that a release liner is temporarily attached to the surface of the adhesive layer 50 until the retardation layer-attached polarizing plate is used. By temporarily attaching the release liner, the adhesive layer is protected until actual use, and the retardation layer-attached polarizing plate can be rolled.
[0013] The thickness of the retardation layer-attached polarizing plate may be set to any appropriate value. In one embodiment, the total thickness of the retardation layer-attached polarizing plate is preferably 150 μm or less, more preferably 140 μm or less, even more preferably 120 μm or less, more preferably 100 μm or less, even more preferably 90 μm or less, and particularly preferably 85 μm or less. The total thickness of the retardation layer-attached polarizing plate may be, for example, 30 μm or more. The total thickness of the retardation layer-attached polarizing plate refers to the sum of the thicknesses of the polarizing plate, the retardation layer, the resin film, and the adhesive layer for laminating them (that is, the total thickness of the retardation layer-attached polarizing plate does not include the thickness of the outermost pressure-sensitive adhesive layer and the thickness of the release liner that may be temporarily attached to the surface of the outermost pressure-sensitive adhesive layer).
[0014] The components of the retardation layer-attached polarizing plate will be described in more detail below.
[0015] B. Polarizing plate As described above, the polarizing plate includes a polarizer. The polarizing plate preferably includes a polarizer, a first protective layer laminated on one surface of the polarizer, and a second protective layer laminated on the other surface of the polarizer. The thickness of the polarizing plate can be set to any appropriate value. The thickness of the polarizing plate is preferably 45 μm to 85 μm, more preferably 50 μm to 80 μm, and even more preferably 55 μm to 75 μm. If the thickness of the polarizing plate is within the above range, the occurrence of interference unevenness and dents can be further suppressed. As described above, the polarizing plate is preferably laminated with the second retardation layer via an adhesive layer. If laminated via an adhesive layer, the occurrence of interference unevenness and dents can be further suppressed.
[0016] B-1.Polarizer A polarizer is typically composed of a resin film containing a dichroic material (typically, iodine). As the resin film, any appropriate resin film that can be used as a polarizer can be adopted. The resin film is typically a polyvinyl alcohol resin (hereinafter, referred to as "PVA resin") film. The resin film may be a single-layer resin film or a laminate of two or more layers.
[0017] A specific example of a polarizer composed of a single layer of resin is a PVA-based resin film that has been subjected to a dyeing treatment with iodine and a stretching treatment (typically, uniaxial stretching). The dyeing with iodine is performed, for example, by immersing the PVA-based resin film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be performed after the dyeing treatment or while dyeing. Alternatively, the film may be stretched and then dyed. If necessary, the PVA-based resin film is subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based resin film in water and washing it before dyeing, not only can dirt and antiblocking agents on the surface of the PVA-based resin film be washed off, but also the PVA-based resin film can be swelled to prevent uneven dyeing.
[0018] Specific examples of polarizers obtained using a laminate include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of the PVA, and to achieve high optical properties. At the same time, by increasing the orientation of the PVA in advance, problems such as a decrease in the orientation or dissolution of the PVA when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation disorder and the decrease in the orientation of the polyvinyl alcohol molecules can be suppressed compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained through a treatment process in which the laminate is immersed in a liquid, such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction by the drying shrinkage treatment.The obtained laminate of resin substrate / polarizer may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the laminate of resin substrate / polarizer, and any suitable protective layer may be laminated on the peeled surface depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP-A-2012-73580 (Patent No. 5414738) and Japanese Patent No. 6470455. The entire disclosures of these publications are incorporated herein by reference.
[0019] The thickness of the polarizer is preferably 1 μm to 30 μm, more preferably 1 μm to 25 μm, further preferably 1 μm to 15 μm, further more preferably 1 μm to 10 μm, and particularly preferably 1 μm to 8 μm. When the thickness of the polarizer is within the above range, the retardation layer-attached polarizing plate can be made thinner.
[0020] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance Ts of the polarizer is preferably 40% to 48%, more preferably 41% to 46%. The degree of polarization P of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more. The single transmittance is typically a Y value measured using an ultraviolet-visible spectrophotometer and subjected to luminosity correction. The degree of polarization is typically calculated by the following formula based on the parallel transmittance Tp and crossed transmittance Tc measured using an ultraviolet-visible spectrophotometer and subjected to luminosity correction. Degree of polarization (%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0021] B-2.Protective layer As described above, the polarizing plate preferably includes a first protective layer 12 laminated on one surface of the polarizer and a second protective layer 13 laminated on the other surface of the polarizer. The first protective layer 12 and the second protective layer 13 are formed of any appropriate film that can be used as a protective layer for a polarizer. Specific examples of materials that are the main components of the film include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylics, and acetates. Other examples include thermosetting resins or ultraviolet-curing resins such as (meth)acrylics, urethanes, (meth)acrylic urethanes, epoxys, and silicones. Other examples include glassy polymers such as siloxane polymers. Also usable is the polymer film described in JP 2001-343529 A (WO01 / 37007). As the material of this film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain, and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain can be used, for example, a resin composition containing an alternating copolymer of isobutene and N-methylmaleimide, and an acrylonitrile-styrene copolymer. The polymer film can be, for example, an extrusion molded product of the above resin composition.
[0022] The polarizing plate with a retardation layer is typically placed on the viewing side of an image display device, and the first protective layer 12 is typically placed on the viewing side. Therefore, the first protective layer 12 may be subjected to a surface treatment such as a hard coat treatment, an anti-reflection treatment, an anti-sticking treatment, or an anti-glare treatment, as necessary.
[0023] The thickness of the first protective layer and the second protective layer is preferably 10 μm to 50 μm, more preferably 10 μm to 30 μm. The thickness of the first protective layer and the second protective layer may be the same or different. When a surface treatment is applied, the thickness of the outer protective layer (first protective layer 12) includes the thickness of the surface treatment layer.
[0024] C. Retardation layer As described above, the first retardation layer and the second retardation layer are liquid crystal alignment solidified layers. When the retardation layer is a liquid crystal alignment solidified layer, dents may become more noticeable when the retardation layer is attached to an image display panel. In addition, interference unevenness may occur due to thin film interference of the liquid crystal alignment solidified layer. As described above, in the embodiment of the present invention, the first retardation layer is a liquid crystal alignment solidified layer, an adhesive layer having a thickness of 2 μm to 8 μm, and a second retardation layer is a liquid crystal alignment solidified layer, in this order. By laminating the retardation layer which is a liquid crystal alignment solidified layer via an adhesive layer having a thickness of 2 μm to 8 μm, it is possible to suppress both interference unevenness and dents. The retardation layer may further include an alignment film and / or a substrate. As described above, the slow axis of the first retardation layer and the absorption axis of the polarizer intersect, and the slow axis of the first retardation layer and the slow axis of the second retardation layer intersect. The angle between the slow axis of the first retardation layer and the absorption axis of the polarizer, and the angle between the slow axis of the first retardation layer and the slow axis of the second retardation layer can be set to any appropriate value depending on the design. The angle between the slow axis of the first retardation layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and even more preferably 12° to 16°. The angle between the slow axis of the second retardation layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and even more preferably 72° to 76°. In this embodiment, the first retardation layer and the second retardation layer may exhibit a reverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, may exhibit a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or may exhibit a flat wavelength dispersion characteristic in which the retardation value hardly changes depending on the wavelength of the measurement light. In this section, the first retardation layer and the second retardation layer are collectively referred to as the retardation layer. When it is necessary to distinguish between the first retardation layer and the second retardation layer, the terms "first" and "second" are used.
[0025] The first retardation layer preferably has a Re(550) of 200 nm to 300 nm, and the angle formed between the slow axis of the first retardation layer and the absorption axis of the polarizer is 10° to 20°. Also, the second retardation layer preferably has a Re(550) of 100 nm to 190 nm, and the angle formed between the slow axis of the second retardation layer and the absorption axis of the polarizer is 70° to 80°. In this embodiment, either one of the first retardation layer and the second retardation layer can function as a λ / 4 plate and the other can function as a λ / 2 plate. For example, when the first retardation layer functions as a λ / 2 plate and the second retardation layer functions as a λ / 4 plate, the Re(550) of the first retardation layer is preferably 200 nm to 300 nm, more preferably 200 nm to 270 nm, still more preferably 210 nm to 260 nm, and particularly preferably 230 nm to 260 nm. The Re(550) of the second retardation layer is preferably 100 nm to 200 nm, more preferably 100 nm to 170 nm, still more preferably 110 nm to 150 nm, and particularly preferably 110 nm to 130 nm.
[0026] The thickness of the first retardation layer can be adjusted, for example, so as to obtain a desired in-plane retardation of the λ / 2 plate. The thickness of the first retardation layer is, for example, 2.0 μm to 4.0 μm. The thickness of the second retardation layer can be adjusted, for example, so as to obtain a desired in-plane retardation of the λ / 4 plate. The thickness of the second retardation layer is, for example, 0.5 μm to 2.5 μm.
[0027] At least one of the first retardation layer and the second retardation layer typically exhibits a refractive index characteristic showing a relationship of nx > ny = nz. Note that "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny > nz or ny < nz may occur. The Nz coefficient of the retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3.
[0028] In this embodiment, the liquid crystal compound used in the first retardation layer and the second retardation layer may be, for example, a liquid crystal compound having a nematic liquid crystal phase (nematic liquid crystal). For example, a liquid crystal polymer or a liquid crystal monomer may be used as such a liquid crystal compound. The liquid crystal compound may exhibit liquid crystallinity by either lyotropic or thermotropic mechanism. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination.
[0029] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a crosslinkable monomer. This is because the liquid crystal monomer can be polymerized or crosslinked (i.e., cured) to fix the alignment state of the liquid crystal monomer. After the liquid crystal monomer is aligned, for example, the liquid crystal monomers can be polymerized or crosslinked with each other to fix the alignment state. Here, a polymer is formed by polymerization, and a three-dimensional network structure is formed by crosslinking, but these are non-liquid crystals. Therefore, the formed retardation layer does not undergo transition to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes specific to liquid crystal compounds, for example. As a result, the retardation layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.
[0030] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and further preferably 60°C to 90°C.
[0031] Any suitable liquid crystal monomer can be used as the liquid crystal monomer. For example, the polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445 can be used. Specific examples of such polymerizable mesogen compounds include BASF's product name LC242, Merck's product name E7, and Wacker-Chem's product name LC-Sillicon-CC3767. As the liquid crystal monomer, a nematic liquid crystal monomer is preferable. Specific examples of the liquid crystal compound and the details of the method for forming the alignment solidification layer are as described above.
[0032] Although the first retardation layer functions as a λ / 2 plate and the second retardation layer functions as a λ / 4 plate, the first retardation layer may be a λ / 4 plate and the second retardation layer may be a λ / 2 plate. In addition, the angle between the axis angle of the first retardation layer and the absorption axis of the polarizer is 10° to 20° (about 15°) and the angle between the axis angle of the second retardation layer and the absorption axis of the polarizer is 60° to 80° (about 75°) in the above description, but the angle between the slow axis of the first retardation layer and the absorption axis of the polarizer may be about 75°, and the angle between the slow axis of the second retardation layer and the absorption axis of the polarizer may be about 15°.
[0033] D. Adhesive layer As described above, the first retardation layer and the second retardation layer are laminated via an adhesive layer having a thickness of 2 μm to 8 μm. If the adhesive layer has a thickness of 2 μm to 8 μm, it is possible to simultaneously suppress the occurrence of dents and suppress interference unevenness, which have been difficult to achieve up until now. The thickness of the adhesive layer is preferably 3 μm to 7 μm, and more preferably 4 μm to 6 μm.
[0034] As described above, the adhesive layer may be an adhesive layer or a pressure-sensitive adhesive layer. A pressure-sensitive adhesive layer is preferable. If the adhesive layer is a pressure-sensitive adhesive layer, a retardation layer-attached polarizing plate in which the occurrence of interference unevenness and dents is further suppressed can be provided.
[0035] D-1.Adhesive layer When the adhesive layer is a pressure-sensitive adhesive layer, the adhesive layer may be formed of any suitable pressure-sensitive adhesive. Specific examples of pressure-sensitive adhesives include acrylic pressure-sensitive adhesives, rubber pressure-sensitive adhesives, silicone pressure-sensitive adhesives, polyester pressure-sensitive adhesives, urethane pressure-sensitive adhesives, epoxy pressure-sensitive adhesives, and polyether pressure-sensitive adhesives. By adjusting the type, number, combination, and compounding ratio of monomers forming the base resin of the pressure-sensitive adhesive, as well as the compounding amount of the crosslinking agent, reaction temperature, reaction time, etc., a pressure-sensitive adhesive having desired properties according to the purpose can be prepared. The base resin of the pressure-sensitive adhesive may be used alone or in combination of two or more types. From the viewpoints of transparency, processability, durability, etc., an acrylic pressure-sensitive adhesive (acrylic pressure-sensitive adhesive composition) is preferred.
[0036] The acrylic pressure-sensitive adhesive typically contains a (meth)acrylic polymer as a main component, and the (meth)acrylic polymer may be contained in the pressure-sensitive adhesive in an amount of, for example, 50% by weight or more, preferably 70% by weight or more, and more preferably 90% by weight or more of the solid content of the pressure-sensitive adhesive.
[0037] The (meth)acrylic polymer contains alkyl (meth)acrylate as a main component as a monomer unit. Here, (meth)acrylate refers to acrylate and / or methacrylate. The alkyl (meth)acrylate may be contained in a proportion of preferably 80% by weight or more, more preferably 90% by weight or more, in the monomer components forming the (meth)acrylic polymer. Examples of the alkyl group of the alkyl (meth)acrylate include linear or branched alkyl groups having 1 to 18 carbon atoms. The average carbon number of the alkyl group is preferably 3 to 9, more preferably 3 to 6.
[0038] The acrylic adhesive may preferably contain a silane coupling agent and / or a crosslinking agent. Examples of the silane coupling agent include an epoxy group-containing silane coupling agent. Examples of the crosslinking agent include an isocyanate-based crosslinking agent and a peroxide-based crosslinking agent. Furthermore, the acrylic adhesive composition may contain an antioxidant and / or a conductive agent. Details of the adhesive layer or the acrylic adhesive composition are described in, for example, JP 2006-183022 A, JP 2015-199942 A, JP 2018-053114 A, JP 2016-190996 A, and WO 2018 / 008712 A, and the descriptions in these publications are incorporated herein by reference.
[0039] D-2.Adhesive layer When the adhesive layer is an adhesive layer, the adhesive layer can be formed of any suitable adhesive. For example, an active energy ray curable adhesive can be used. As the active energy ray curable adhesive, any suitable active energy ray curable adhesive can be used, for example, an ultraviolet ray curable adhesive or an electron beam curable adhesive can be used.
[0040] The active energy ray curable adhesive typically contains a monofunctional component, a polyfunctional component (curing component), and a photopolymerization initiator. The monofunctional component and the polyfunctional component are typically radical polymerizable compounds. Preferred monofunctional components include, for example, higher alkyl esters of (meth)acrylic acid and modified products thereof. Specific examples include isostearyl acrylate, lauryl acrylate, acryloylmorpholine, unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone, and the like. Preferred polyfunctional components include, for example, monomers and / or oligomers having two or more functional groups such as (meth)acrylate groups and (meth)acrylamide groups. Specific examples include polyethylene glycol diacrylate, trimethylpropane triacrylate, and glycerin triacrylate. Specific examples of monofunctional or polyfunctional components other than those mentioned above include tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, phenoxydiethylene glycol acrylate, cyclic trimethylolpropane formal acrylate, dioxane glycol diacrylate, EO-modified diglycerin tetraacrylate, γ-butyrolactone acrylate, N-methylpyrrolidone, hydroxyethyl acrylamide, N-methylol acrylamide, N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide, and 9-vinyl carbazole. In one embodiment, the monofunctional or polyfunctional component has a ring structure. Specific examples include acryloylmorpholine, γ-butyrolactone acrylate, unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone, N-methylpyrrolidone, and 9-vinyl carbazole. The monofunctional or polyfunctional components may each be used alone or in combination of two or more.
[0041] The active energy ray curable adhesive may further contain a cationic polymerizable compound as required. The cationic polymerizable compound may be monofunctional or polyfunctional. Examples of the monofunctional cationic polymerizable compound include p-tert-butylphenyl glycidyl ether and 3-ethyl-3-[(2-ethylhexyl)oxy]oxetane. Examples of the polyfunctional cationic polymerizable compound include 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane. A silane coupling agent may be used as the cationic polymerizable compound. Examples of the silane coupling agent include 3-glycidoxypropyltrimethoxysilane.
[0042] The active energy ray curable adhesive may further contain any suitable additive. For example, a plasticizer (e.g., an oligomer component), a crosslinking agent, a diluent, etc. These additives are used in any suitable content depending on the purpose.
[0043] Details of the active energy ray-curable adhesive are described, for example, in JP 2018-017996 A. The description of the publication is incorporated herein by reference.
[0044] E. Image display device The retardation layer-attached polarizing plate described in the above items A to D can be applied to an image display device. Therefore, the embodiment of the present invention includes an image display device using such a retardation layer-attached polarizing plate. Representative examples of image display devices include liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices and inorganic EL display devices). The image display device according to the embodiment of the present invention can include the retardation layer-attached polarizing plate on the viewing side. The retardation layer-attached polarizing plate can be laminated so that the retardation layer is on the image display cell (e.g., liquid crystal cell, organic EL cell, inorganic EL cell) side (so that the polarizer is on the viewing side). As described above, the retardation layer-attached polarizing plate of the embodiment of the present invention can suppress the occurrence of dents when it is attached to an image display panel. Therefore, the productivity of the image display device can be improved. EXAMPLES
[0045] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified.
[0046] (1) Thickness The thickness of 10 μm or less was measured using an interference film thickness meter (manufactured by Otsuka Electronics, product name "MCPD-3000"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C").
[0047] (2) Load-bearing compression evaluation The retardation layer-attached polarizing plate obtained in the examples and comparative examples was cut into a length of 1 cm and a width of 1 cm to prepare a sample. The second adhesive layer of the sample was attached to an aluminum reflector (manufactured by Toray Film Processing Co., Ltd., product name "Cerapeel DMS-X42", total light reflectance: 86%). Then, the sample was placed on a glass plate (manufactured by Matsunami Glass Industry Co., Ltd., thickness: 0.7 mm) so that the surface of the hard coat layer of the sample was in contact with the glass plate. Then, a weight was placed on a cone-shaped indenter (diameter 1.5 mm) from the aluminum reflector side via a polyethylene terephthalate (PET) sheet (manufactured by Toray Industries, Inc., thickness 80 μm) and pressed for 10 seconds. The weight (load) of the weight was changed to 300 g (1.7 MPa), 400 g (2.2 MPa), and 500 g (2.8 MPa), and measurements were performed. After that, the weight and the indenter were removed, and the surface of the retardation layer-attached polarizing plate that had been in contact with the glass plate was visually observed in reflection at a polar angle of 30° to 60° and around one azimuth angle to confirm the presence or absence of dents, and the maximum load at which no dents were observed was defined as the load capacity. In addition, when the surface of the retardation layer-attached polarizing plate is defined as the X-axis and the Y-axis, and the axis perpendicular to the XY plane is defined as the Z-axis, the angle inclined from the Z-axis to the XY plane direction was defined as the polar angle (θ), and the MD direction of the polarizing plate used in the retardation layer-attached polarizing plate was defined as 0°, and the measurement angle defined between the MD direction of this polarizing plate and the counterclockwise direction was defined as the azimuth angle (φ).
[0048] (3) Interference unevenness The retardation layer-attached polarizing plate obtained in the examples and comparative examples was attached to a V3 reflector (manufactured by NEODIS) via the outermost adhesive layer. Next, an acrylic adhesive was applied to the polarizing plate side of the retardation layer-attached polarizing plate to form an adhesive layer with a thickness of 100 μm, and then a glass plate (manufactured by Matsunami Glass Industry Co., Ltd., thickness: 0.7 mm) was attached via the adhesive layer. After that, the reflection was observed visually under a fluorescent lamp (three-wavelength tube), and the evaluation was performed according to the following criteria. The observation was performed for polar angles of 20° to 60° and for an azimuth angle of one revolution. Note that unevenness visible even under sunlight was not included in the interference unevenness. ○ (Good): No visible streaks or irregular irregularities in pink, green or black caused by interference light. △ (Fair): Irregular unevenness due to interference light visible in pink, green, and black is visible, but no streaky unevenness is visible. × (room for improvement): Stripes of unevenness caused by interference light that appears pink, green, and black are visible.
[0049] (4) Judgment The suitability of the retardation layer-attached polarizing plate for use in an image display device was evaluated according to the following criteria. 〇〇 (best): Load bearing indentation rating is 2.6 MPa or more, or interference unevenness is 〇 (good) ○ (Good): The load resistance is 2.0 MPa or more, or the interference unevenness is △ (Fair) or ○ (Good). × (room for improvement): The load resistance is 2.0 MPa or less, or the interference unevenness is × (room for improvement).
[0050] [Production Example 1] Preparation of adhesive composition 1. Preparation of Base Polymer A monomer mixture containing 94.9 parts by weight of butyl acrylate (BA), 5 parts by weight of acrylic acid (AA), and 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA) was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Next, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with ethyl acetate for 100 parts by weight of the monomer mixture (solid content), and nitrogen gas was introduced while gently stirring to replace the nitrogen. The liquid temperature in the flask was kept at around 55°C and a polymerization reaction was carried out for 7 hours. Then, ethyl acetate was added to the resulting reaction solution to obtain a solution of a (meth)acrylic polymer with a weight average molecular weight of 2 million, adjusted to a solid content concentration of 30%.
[0051] 2. Preparation of acrylic adhesive composition An acrylic adhesive composition was prepared by blending 0.6 parts by weight of an isocyanate crosslinking agent (trimethylolpropane / tolylene diisocyanate adduct, manufactured by Tosoh Corporation, product name "Coronate L") and 0.1 parts by weight of a silane coupling agent (product name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.) with 100 parts by weight of the solid content of the obtained (meth)acrylic polymer solution.
[0052] [Production Example 2] Preparation of UV-curable adhesive A UV-curable adhesive A was prepared by mixing 50 parts by weight of unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone (manufactured by Daicel Corporation, product name "Placcel FA-1DDM"), 10 parts by weight of polyethylene glycol diacrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Acrylate 9EG-A"), 20 parts by weight of acryloyl morpholine, 15 parts by weight of acrylic polymer (manufactured by Toagosei Co., Ltd., product name "ARUFON UP-1190"), 3 parts by weight of photopolymerization initiator (manufactured by IGM Resins, product name "Omnirad 907"), and 2 parts by weight of photopolymerization initiator (manufactured by Nippon Kayaku Co., Ltd., product name "KAYACURE-DETX-S").
[0053] [Example 1] <Preparation of polarizing plate> 1. Preparation of Polarizer As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizer would be the desired value (dyeing treatment). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizer having a thickness of 6 μm was formed on the resin substrate, and a polarizing plate having a resin substrate / polarizer structure was obtained. The single transmittance Ts of the polarizer was 43.3%.
[0054] 2. Preparation of Polarizing Plates An HC-COP film was attached to the surface of the obtained polarizer (the surface opposite to the resin substrate) via an ultraviolet-curing adhesive. The HC-COP film was a film in which an HC layer (4 μm thick) was formed on a cycloolefin resin (COP) film (25 μm thick), and the COP film was attached to the polarizer side. The COP film had a Re (550) of 135 nm. Next, the resin substrate was peeled off, and a triacetyl cellulose (TAC) film (20 μm thick) was attached to the peeled surface via an ultraviolet-curing adhesive. In this way, a polarizing plate having a configuration of HC layer / COP film (protective layer) / polarizer / TAC film (protective layer) was obtained.
[0055] 3. Preparation of polarizing plate with retardation layer A liquid crystal composition (coating liquid) was prepared by dissolving 10 g of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: product name "Paliocolor LC242", represented by the following formula) and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: product name "Irgacure 907") in 40 g of toluene. [ka] The surface of a PET film (thickness 38 μm) was rubbed with a rubbing cloth and subjected to an alignment treatment. The direction of the alignment treatment was set to be 15° from the viewing side with respect to the direction of the absorption axis of the polarizer when it was attached to the polarizing plate. The above liquid crystal coating liquid was applied to this alignment-treated surface with a bar coater, and the liquid crystal compound was aligned by heating and drying at 90° C. for 2 minutes. The liquid crystal layer thus formed was then irradiated with 100 mJ / cm 2 using a metal halide lamp. 2The liquid crystal layer was cured by irradiating the liquid crystal layer with light of 1000 nm to form a first retardation layer, which is a liquid crystal alignment solidified layer, on the PET film. The thickness of the first retardation layer was 2 μm, and the in-plane retardation Re(550) was 270 nm. Furthermore, the first retardation layer had a refractive index distribution of nx>ny=nz. The adhesive obtained in Production Example 2 was applied to the TAC film side surface of the polarizing plate obtained above, and the first retardation layer obtained above was attached via an adhesive layer having a thickness of 1 μm. Then, the PET film was peeled off from the first retardation layer. Separately, a second retardation layer was formed on a PET film in the same manner as above, except that the coating thickness was changed and the orientation treatment direction was set to a 75° direction relative to the absorption axis direction of the polarizer when viewed from the viewing side. The thickness of the second retardation layer was 1 μm, and the in-plane retardation Re (550) was 140 nm. Furthermore, the second retardation layer had a refractive index distribution of nx>ny=nz. The adhesive obtained in Production Example 1 was applied to the PET film peeling surface of the first retardation layer to form an adhesive layer (adhesive layer) having a thickness of 7 μm, and the surface of the second retardation layer obtained above on which the PET film was not laminated was attached. Next, the PET film was peeled off from the second retardation layer, and the adhesive obtained in Production Example 1 was applied to the peeling surface to form an adhesive layer (outermost adhesive layer) having a thickness of 25 μm, and a retardation layer-attached polarizing plate was obtained. The first retardation layer was attached so that the angle between the slow axis of the first retardation layer and the absorption axis of the polarizer was 15°, and the second retardation layer was attached so that the angle between the slow axis of the second retardation layer and the absorption axis of the polarizer was 75°. Until the evaluation, a 38 μm-thick polyethylene terephthalate film (PET film, separator) treated with a silicone-based release agent was attached to the outermost adhesive layer. The results are shown in Table 1.
[0056] [Example 2] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that the thickness of the pressure-sensitive adhesive layer, which was the adhesive layer, was set to 5 μm. The results are shown in Table 1.
[0057] [Example 3] A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that the thickness of the pressure-sensitive adhesive layer, which was the adhesive layer, was set to 3 μm. The results are shown in Table 1.
[0058] [Example 4] A polarizing plate with a retardation layer was obtained in the same manner as in Example 2, except that the thickness of the TAC film attached as a protective layer for the polarizer was 40 μm. The results are shown in Table 1.
[0059] [Example 5] A long roll of polyvinyl alcohol (PVA) resin film (manufactured by Kuraray, product name "PE3000") with a thickness of 30 μm was uniaxially stretched in the longitudinal direction to 5.9 times its original size using a roll stretching machine while simultaneously undergoing swelling, dyeing, crosslinking, and washing processes, and finally a drying process to produce a polarizer with a thickness of 12 μm. A polarizing plate with a retardation layer was obtained in the same manner as in Example 2, except that the polarizer obtained above was used as the polarizer. The results are shown in Table 1.
[0060] Comparative Example 1 Except for changing the thickness of the pressure-sensitive adhesive layer to 20 μm, a retardation layer-attached polarizing plate was obtained in the same manner as in Example 1. The results are shown in Table 1.
[0061] Comparative Example 2 Except for changing the thickness of the pressure-sensitive adhesive layer to 10 μm, a retardation layer-attached polarizing plate was obtained in the same manner as in Example 1. The results are shown in Table 1.
[0062] Comparative Example 3 A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that a 1 μm-thick adhesive layer was formed using the adhesive obtained in Production Example 2 instead of the 7 μm-thick adhesive layer. The results are shown in Table 1.
[0063] Comparative Example 4 A polarizing plate with a retardation layer was obtained in the same manner as in Comparative Example 3, except that the TAC film was not attached to the polarizer. The results are shown in Table 1.
[0064] [Table 1]
[0065] [evaluation] As is clear from Table 1, the retardation layer-attached polarizing plates of the examples of the present invention were able to suppress the occurrence of interference unevenness and dents. [Industrial Applicability]
[0066] The retardation layer-attached polarizing plate according to the embodiment of the present invention can be suitably used in image display devices such as liquid crystal display devices, organic EL display devices, and inorganic EL display devices. [Explanation of symbols]
[0067] 10 Polarizing plate 11 Polarizer 12 Protective layer 13 Protective layer 21 Adhesive layer 31 First retardation layer 32 Second retardation layer 40 Adhesive layer 50 Adhesive layer 100 Polarizing plate with retardation layer
Claims
1. The present invention has, in this order, a polarizing plate including a polarizer; a first retardation layer which is a layer in which a liquid crystal compound is aligned and fixed; an adhesive layer; and a second retardation layer which is a layer in which a liquid crystal compound is aligned and fixed. a slow axis of the first retardation layer intersects with a slow axis of the second retardation layer; a slow axis of the first retardation layer intersects with an absorption axis of the polarizer, The thickness of the adhesive layer is 2 μm to 8 μm.
2. The retardation layer-attached polarizing plate according to claim 1 , wherein the adhesive layer is a pressure-sensitive adhesive layer.
3. 2. The retardation layer-attached polarizing plate according to claim 1, wherein the polarizing plate includes a first protective layer laminated on one surface of the polarizer and a second protective layer laminated on the other surface of the polarizer.
4. 2. The retardation layer-attached polarizing plate according to claim 1, wherein the polarizing plate has a thickness of 45 μm to 85 μm.
5. The retardation layer-attached polarizing plate according to claim 1 , wherein the polarizing plate is laminated to the first retardation layer via an adhesive layer.
6. The first retardation layer has an Re(550) of 200 nm to 300 nm, and the angle between the slow axis of the first retardation layer and the absorption axis of the polarizer is 10° to 20°, The retardation layer-attached polarizing plate according to claim 1, wherein the second retardation layer has an Re(550) of 100 nm to 190 nm, and the angle between the slow axis of the second retardation layer and the absorption axis of the polarizer is 70° to 80°.
7. An image display device comprising the retardation layer-attached polarizing plate according to claim 1 .
8. 8. The image display device according to claim 7, which is an organic electroluminescence display device.
Citation Information
Patent Citations
Control device for vehicular headlight, control method for vehicular headlight, and vehicular headlight system
JP2022014611A